Specific Features of Application of the FAS Order No. 220 in Respect of Determination of Commodity Boundaries of the Merchandise Market (On the Example of the Mineral Wool Market) - DOROGOV, Nikolay I.; KAPITONOV, Ivan A. (Journal of Advanced Research in Law and Economics, 2020)
Authors of this research analyze specific features of application of the Order of the Federal Anti-Monopoly Service (FAS) No. 220 in respect of determination of commodity boundaries of the market and creation of necessary conditions for competition in the mineral wool market. Preliminary determination of the commodities, which was carried out on the basis of analysis of the All-Russian classifiers of products and kinds of economic activity, has shown that in the course of determination of the merchandise market it is necessary to include glass wool, slag wool, and stone wool into one and the same commodity group. Due to the complexity of performance of the comprehensive and representative expert investigation, it is possible to utilize the data of the RF FAS research, which was carried already. Authors of this article describe specific features of determination of the merchandise market through the example of such commodities as ‘the glass wool goods’: this market was subject to analysis of the RF FAS in 2017. Selection of the investigation methods is to be made on the basis of the investigation periods and accessibility of information (among other factors).